Analisis Efektivitas Model Problem Based Learning (PBL) terhadap Peningkatan Hasil Belajar Siswa pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) Kelas XII SMA - Zuhra Munifah Harahap; Jesica Dhea Chyntia; Agung Bakri Sihombing; Dian Armanto (STKIP Subang, 2025)
This study aims to analyze the effectiveness of the Problem Based Learning (PBL) model in improving students’ mathematics learning outcomes on the topic of Systems of Two-Variable Linear Equations (SPLDV). The research subjects were 20 twelfth-grade students of SMA Negeri 1 Percut Sei Tuan, using a quantitative descriptive approach and a one-group pretest–posttest design. The research instrument consisted of an achievement test based on cognitive indicators C4 (analysis), C5 (synthesis), and C6 (evaluation). The results show a clear improvement in students’ learning outcomes after the implementation of PBL. The average pretest score of 16.55 increased to 25.1 on the posttest, while the N-Gain score of 0.63 falls into the medium category. The distribution of learning outcome categories also shifted positively: in the pretest, 7 students were in the low category, 10 in the medium category, and 3 in the high category; whereas in the posttest, no students remained in the low category, 5 were in the medium category, and 15 were in the high category. These findings indicate that the implementation of PBL can enhance students’ analytical skills, problem-solving abilities, and conceptual understanding of SPLDV more deeply, making it an effective instructional model for improving the quality of mathematics learning processes and outcomes.